Crystal structures, magnetic properties, and DFT calculation of B-site defected 12L-perovskites Ba2La2MW2O12 (M = Mn, Co, Ni, Zn). (7th August 2017) - Doi, Yoshihiro; Wakeshima, Makoto; Tezuka, Keitaro; Shan, Yue Jin; Ohoyama, Kenji; Lee, Sanghyun; Torii, Shuki; Kamiyama, Takashi; Hinatsu, Yukio
Abstract: The synthesis, crystal structures and magnetic properties of Ba2 La2 MW2 O12 (M = Mn, Co, Ni, Zn) were investigated. They crystallize in the 12-layer polytype of the perovskite structure with a regular cation defect in the B-site. The results of neutron diffraction measurements reveal that they adopt a rhombohedral structure with a space group R − 3 and have a cation ordering between Ba and La ions in the A-site. In these compounds, the magnetic M ions form the 2D triangular lattice. From the results of magnetic measurements, the ferromagnetic ordering of M 2+ ions for M = Co ( T C = 1.3 K) and Ni (6.2 K) and the paramagnetic behavior ( T > 1.8 K) with an antiferromagnetic interaction for M = Mn are observed. From the DFT calculation, their band structures and magnetic interactions are discussed.